An adaptive network model of the role of the microbiome-gut-brain axis in insomnia. (March 2023) - Banerjee, Sulagna; Chitty, Claudia; Lee, Quinn; Treur, Jan
Abstract: This paper presents an adaptive network model simulating the role of the gut microbiome for triggering biological mechanisms that alter the circadian cycle, mood and insomnia via the microbiome-gut-brain axis. Simulation graphs provide insight into how these immune and endocrine pathways interact with each other when the levels of the probiotics, Lactobacillus and Bifidobacteria, and pathogenic bacteria were altered. Varying these factors in simulations produced different outcomes for insomnia and sleep deprivation.